ADAPTABILITY STRATEGIES OF LEARNERS AGAINST COVID-19 UNCERTAINTY (Proceedings of the International Conference on Education, 2021)
New infectious diseases, especially one of the magnitudes of COVID-19, leads to complex situations for individuals and communities alike. Particularly in higher education, learners faced a surrealist world in which education shifted abruptly to an online setting because of the virus. Regardless of their field of study, they had to apply coping strategies to adapt and incorporate new values, beliefs, and perspectives into a new learning environment. Universities must foster educational opportunities to train learners on these capacities to prepare professionals for their success in their profession. This study’s objective was to assess these adaptability strategies that higher-education learners had to tackle the uncertainty of the coronavirus pandemic. A quantitative approach was considered with a descriptive and cross-sectional design. The convenience sample consisted of 34 learners in the final year of their medical program. As an instrument, an adaptation of the Proactive Coping Inventory was used with a 5-level Likert scale where 1 stands for total disagreement and 5 with total agreement. According to the results, students use more than one strategy to cope with difficult situations. The mean obtained in the control strategy was 3.98, curiosity 3.18, confidence 3.02, and concern was 2.97. The ANOVA test showed that there is no significant difference in the dimensions (p-value of 0.062). These results indicate that students had the intellectual curiosity to propose new personal and professional development goals and monitor the scope of those through self-regulation. Institutions need to learn from what they implemented amid the pandemic and incorporate best practices for the new normality ahead.
Keywords: educational innovation; higher education; professional education; medical education; coping strategies; pandemic adaptations